Verbalizando morcegos estritamente pessoais & intransferíveis: narrativa e experiência em Morangos mofados, de Caio Fernando Abreu - Coimbra, Rosicley Andrade (2019)
The present thesis aims to investigate two issues in the book Morangos Mofados (1982) by Caio Fernando Abreu: narrative and experience. We start from the idea that this book has great representation within the Brazilian literature because it arises at a tense moment in the Brazilian political scene: the years of transition from the military regime (1964-1985) to the redemocratization. In this sense, Morangos Mofados can be read as a set of stories in which the traumatic experiences of the military regime are configured in their narratives, as well as the inability to narrate the defeat of a generation marked by authoritarianism. Through a bibliographical research we intend to investigate how the stories of the various individuals who live in the book are represented. At first, we detected characters still stuck in the past, but feeling the overwhelming weight of the present, are soon unable to verbalize their experiences or make future and collective projects. At another time, the characters will face images of themselves and an instant of confronting the past. The fragmentation of narratives is an indicative that the context required new forms of representation and literature itself abandoned the path of engagement and sought new paths. From this perspective, Morangos Mofados will make a deep critical reflection about the experiences of Brazil’s recent past, involving the consequences of the military dictatorship and the inability to narrate about these events. The melancholy that permeates the stories, as well as the insistence on narrating and the fragmentation can be seen as forms of rewriting of the recent history of the country, using files that translate this moment by the literary way, finding in the anonymous matter propitious to tell the other side of history – a history against the grain. The theoretical and critical studies of Walter Benjamin, Giorgio Agamben, Jeanne Marie Gagnebin, Silviano Santiago, Idelber Avelar, Nelly Richard and others will be primordial to think about issues related to the crisis of the transmissibility of experience and aspects of postdictatorial literature, while reflections of Jaime Ginzburg, Flora Süssekind, Luana Teixeira Porto, Arturo Gouveia, among others, will have a relevant role in the analyzes of Morangos mofados.